Growing up unequal? Socioeconomic disparities in mental disorders throughout childhood in Finland - Maria Vaalavuo; Ripsa Niemi; Jaana Suvisaari (Elsevier, 2022)
Problems in mental health and socioeconomic health inequalities during childhood and adolescence are receiving important scientific and political attention. This in mind, we study how current family income and parental education are associated with psychiatric disorders among children in a well-developed welfare state, Finland. To gain a deeper understanding of how these disparities develop through early life course, we study the differences between genders, age groups, types of mental disorders, and also take into account the role of parental mental disorders. We exploit high-quality Finnish register data containing the whole population aged 4-17 with information on their families and parents. Our results of linear probability models show that lower parental education is consistently associated with higher probability of mental disorders throughout childhood, although some gender and disorder-specific differences are also identified. Interestingly, household income is related to mental health in more complex ways, having both negative and positive associations with psychiatric disorders. Inequalities are stronger among boys than girls, and the strongest associations are found among boys aged 7-12 and girls aged 13-17. Parental mental disorders increase the risk of children's psychiatric disorders but do not explain socioeconomic disparities. Considering the negative effects of mental problems on socioeconomic outcomes, inequalities in childhood mental health can be expected to reinforce other social inequalities in later life and should therefore be a focus of interventions.